HYDROTHERMAL CARBONIZATION OF BIOMASS WASTE BY USING A STIRRED REACTOR: AN INITIAL EXPERIMENTAL RESULTS - Herlian Eriska; Kania Dewi; Ari Darmawan Pasek; Enri Damanhuri (Reaktor, 2016)
Hydrothermal carbonization (HTC) is a thermochemical process used to convert wet biomass waste become a coal-like material with higher carbon content called hydrochar. In this study, design and performance test of hydrothermal carbonization prototype reactor is done. Stirred reactor was made of stainless steel 304 with volume of 1 Liter and electric heater as a heating mantle. The HTC reactor was utilized to perform the carbonization of three materials (paper, left-rice, and woodchip) as substrates, in order to study the influence of the temperature conditions on the hydrochar produced. The substrates represent major component in municpal solid waste (MSW). The study showed that chemical and physical properties of several feedstock and hydrochar varied as a function of reaction temperature. HTC is operated in batch at temperatures of 160°, 190° and 220oC, 60 min of reaction time, and 1 MPa initial pressure of nitrogen gas. Three of product were collected from the process with primary material balance. Results showed the products change as the temperature increased. The results suggested that hydrothermal treatment of biomass waste to solid fuel gave high heating value (HHV) with value of 5231.3, 4569.5, and 5422.7 kcal/kg for paper, left-rice, and woodchip respectively after product dried naturally.